An investigation on fatigue behavior of AA2024 aluminum alloy sheets in fuselage lap joints. (August 2021) - Masoudi Nejad, Reza; Berto, Filippo; Tohidi, Mohammadreza; Jalayerian Darbandi, Ahmad; Sina, Nima
Highlights: This paper provides the crack growth and fatigue life estimation of the fuselage lap joints. The optimal model is obtained using the finite element method. A 3D boundary element model has been applied to estimate the fatigue life. Failure of rivet joints in aluminum 2024 sheets was analyzed to identify the cause. Numerical results are in good agreement with those achieved in experimental test. Abstract: The purpose of this paper is to estimate the fatigue life of AA2024 aluminum alloy sheets in riveted joints under the influence of cyclic loading. First, the factors affecting the plastic equivalent strain resulting from the riveting process have been identified using the finite element method. For this purpose, a three-dimensional elastoplastic model is used for simulation. The relevant geometrical parameters such as the rivets shank length, the rivets shank diameter, and dimensional tolerances as well as pattern of where the rivets are and the material of the riveted joints are determined and subsequently the fatigue life of the aluminum joint is obtained by experimental tests. Then the fatigue life of the riveted joints is calculated using the Paris equation. To prove the validity of the analytical results, numerical modeling and experimental tests are performed on AA2024 aluminum alloy sheets in riveted joints. Numerical analysis has been performed using linear fracture mechanics and boundary element method (BEM) for the fatigue crack growth of AA2024 aluminum alloy sheets in riveted joints. Finally, the results of the analytical method for fatigue life are compared with experimental tests and numerical method that results in acceptable achievements.